Peran Badan Pertanahan Nasional dalam Mengatasi Masalah Tumpang Tindih Sertifikat Tanah - Aprilianti, Dwi (JURNAL PENELITIAN SERAMBI HUKUM, 2026)
The existence of double certificates is one of the problems that arises in the land registration process, which is also known as overlap in relation to land rights issued by the local land office. This can happen when more than one land title certificate is issued on one plot of land. Of course, this double certificate will result in a civil dispute because it could harm the rights of each party. The aim of this research is to gain an understanding of the role of the national land agency in overcoming the problem of overlapping land certificates. This research is a normative legal study adopting a conceptual approach by examining views and theories in the field of law as well as a statutory approach to researching regulations related to existing legal issues. The occurrence of duplicate certificates which results in legal defects such as fake certificates and duplicate certificates because they are influenced by internal and external factors. Internal factors, namely the Basic Agrarian Law and related regulations in its implementation, are not implemented responsibly and consistently. External factors include people who do not understand the laws and regulations that apply in the land sector, especially regarding procedures for making land certificates.